Controlled Synthesis of Ag2Te@Ag2S Core–Shell Quantum Dots with Enhanced and Tunable Fluorescence in the Second Near‐Infrared Window. Issue 14 (12th March 2020) - Zhang, Yejun; Yang, Hongchao; An, Xinyi; Wang, Zan; Yang, Xiaohu; Yu, Mengxuan; Zhang, Rong; Sun, Ziqiang; Wang, Qiangbin
Abstract: Fluorescence in the second near‐infrared window (NIR‐II, 900–1700 nm) has drawn great interest for bioimaging, owing to its high tissue penetration depth and high spatiotemporal resolution. NIR‐II fluorophores with high photoluminescence quantum yield (PLQY) and stability along with high biocompatibility are urgently pursued. In this work, a Ag‐rich Ag2 Te quantum dots (QDs) surface with sulfur source is successfully engineered to prepare a larger bandgap of Ag2 S shell to passivate the Ag2 Te core via a facile colloidal route, which greatly enhances the PLQY of Ag2 Te QDs and significantly improves the stability of Ag2 Te QDs. This strategy works well with different sized core Ag2 Te QDs so that the NIR‐II PL can be tuned in a wide range. In vivo imaging using the as‐prepared Ag2 Te@Ag2 S QDs presents much higher spatial resolution images of organs and vascular structures as compared with the same dose of Ag2 Te nanoprobes administrated, suggesting the success of the core–shell synthetic strategy and the potential biomedical applications of core–shell NIR‐II nanoprobes. Abstract : Ag2 Te@Ag2 S core–shell quantum dots (QDs) with tunable emission are successfully prepared from the NIR‐IIa to NIR‐IIb window via a facile colloidal route, which greatly enhances the quantum yield of Ag2 Te QDs and significantly improves the stability of Ag2 Te QDs. In vivo imaging results suggest the advantages and potential biomedical applications of the new NIR‐II nanoprobes.